Implementasi Program Keagamaan sebagai Upaya Pembinaan Akhlak Peserta Didik - Amira Putri Salsabila; Zahriyah Simargolang (An-Nuha, 2026)
This study aims to describe the implementation of religious programs and analyze how these programs contribute to the moral development of students at SMP Negeri 40 Padang. This research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that the religious programs at SMP Negeri 40 Padang are implemented through several activities, including weekly Qur’anic recitation (tadarus), tahfizh, the recitation of Asmaul Husna, congregational zuhr prayer, the Students’ Prayer Movement (GPS), muhadarah, and the Qur’anic Learning Program (TPQ). All activities are carried out systematically and supported by Islamic Education teachers, the vice principal for student affairs, and other teachers. The results show that the implementation of religious programs has a significant contribution to students’ moral development, particularly in aspects of discipline, manners, responsibility, honesty, and spiritual awareness. These religious activities function as a habituation process that shapes positive behavior through continuous and structured worship practices. Furthermore, the school’s religious environment and the teachers’ role modeling strengthen the internalization of moral values among students. Therefore, the religious programs at SMP Negeri 40 Padang are considered effective in supporting students’ moral development and may serve as a relevant model for other schools in strengthening character education based on Islamic values.